Vascular Dysfunction in Aging and Related Disease - Deshpande, Dr. Pranjali; Howale, Dr. Deepak S. (International Journal of Innovative Research in Medical Science, 2018)
The process that importantly impact on their health status of elder people represents vascular aging. Aging process is one of the factors for main risk for the development of cardiovascular disease (CVD). Many studies show that 50% clinical CVD present in the elderly. Many studies epidemiologically show that risk factor for CVD is age. Actually the prevalence and incidence of coronary heart disease, hypertension, congestive heart failure and stroke steeply increase with age. Individuals in 75-84 year old as compared to 35-44 year old people increase in death rates for heart disease and cerebrovascular disease there is a 60 fold and 80 fold respectively. The endothelium plays an active role in process of platelet adhesion and inflammation. C-reactive protein (CRP) is one of the acute phase proteins. The aim of study was screening of population with asymptomatic individuals for risk markers of hypertension and atherosclerosis leading to vascular events and also investigation of recently detected hypertension and diabetes mellitus. Materials and methods: This study was carried out in Zydus Medical College and hospital, Dahod. In this study total 200 indivuals were included. 2 control groups were include as 38 Group I healthy controls (Age range: 18-24 years) and 65 Group II controls included apparently healthy, asymptomatic individuals whose blood pressure values did not exceed 139/89 and whose fasting blood sugar (FBS) values were B110 mg% (Age range: 25-60 years). It is also grouped as group III and Group IV where in group III include recent/ newly detected hypertension whose blood pressure value range _> 140/90 without medication (age range: 25-60 years) and group IV include individuals suffered from both hypertension and diabetes mellitus (FBS level of_>110mg% with age range 25-60 years. Fasting blood sugar was done by the glucose oxidaseperoxidase method (GOD-POD method). Results: hsCRP and plasma hemoglobin are associated with endothelial dysfunction and increases both with age as well as in disease condition. Endothelial dysfunction was demonstrated in asymptomatic young adults and children with risk factors for atherosclerosis as smoking cigarette and hypercholesterolemia. Conclusion: The presence of diseases such as hypertension or diabetes alone could affect increasing lipid profile value which may be strongly affected by increasing age. Therefore this study shows hsCRP and plasma hemoglobin associated with endothelial dysfunction and increase both with age as well as in disease condition with diabetes mellitus and hypertension together.